Pyrolysis - Samer, Mohamed (IntechOpen, 2017)
This book provides useful information about pyrolysis, which includes the pyrolysis of biomass and pyrolysis of fossil fuels and petrochemicals. Additionally, this book elucidates and illustrates further innovative pyrolysis processes such as catalytic pyrolysis, spray pyrolysis, and microwave-assisted pyrolysis. This book discusses the production of semiconductors and nanomaterials through the pyrolysis process.